Molecular epidemiology of invasive Haemophilus influenzae disease in Portugal: an update of the post-vaccine period, 2011-2018 - Heliodoro, Catarina Isabel Moreira (2021)
Haemophilus influenzae reference laboratory from Portugal characterized the entire collection of 260 H. influenzae invasive isolates received between 2011 and 2018, with the purpose of updating the last published data (2002-2010). Capsular serotypes and antimicrobial susceptibility patterns were determined. The ftsI gene encoding the transpeptidase domain of PBP3 was sequenced for β-lactamase-negative ampicillin-resistant (BLNAR) isolates. Multilocus sequence typing (MLST) was performed to examine genetic relatedness among isolates. The majority of H. influenzae invasive isolates are nonencapsulated (NTHi-79.2%). Among encapsulated isolates (20.8%), the most characterized serotype was serotype b (13.5%), followed by serotype f (3.1%), serotype a (2.7%), and serotype e (1.5%). In contrast to NTHi that mainly affected the elderly (64.0%; ≥ 65 years old), most encapsulated isolates were characterized in preschool children (55.6%). Comparing the two periods, β-lactamase production increased from 10.4 to 13.5% (p = 0.032) and low-BLNAR (MIC ≥ 1 mg/L) isolates from 7.7 to 10.5% (p = 0.017). NTHi showed high genetic diversity (60.7%), in opposition to encapsulated isolates that were clonal within each serotype. Interestingly, ST103 and ST57 were the predominant STs among NTHi, with ST103 being associated with β-lactamase-producers and ST57 with non-β-lactamase-producers. In Portugal, susceptible and genetically diverse NTHi H. influenzae continues to be responsible for invasive disease, mainly in the elderly. Nevertheless, we are now concerned with Hib circulating in children we believe to have been vaccinated. Our data reiterates the need for continued surveillance, which will be useful in the development of public health prevention strategies.